2023
DOI: 10.1038/s41598-022-27349-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservation and diversification of auditory neural circuits that process courtship songs in Drosophila

Abstract: Acoustic communication signals diversify even on short evolutionary time scales. To understand how the auditory system underlying acoustic communication could evolve, we conducted a systematic comparison of the early stages of the auditory neural circuit involved in song information processing between closely-related fruit-fly species. Male Drosophila melanogaster and D. simulans produce different sound signals during mating rituals, known as courtship songs. Female flies from these species selectively increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…We used restricted mean time lost (RMTL) as an indicator of the cumulative copulation rate to evaluate this change, where a larger RMTL reflects higher copulation acceptance (Fig. 4 E ; See Materials and Methods for details) (15). We found that the response of experienced females to the conspecific song, but not to the heterospecific song, was significantly reduced in the Dop1R2 knockdown group when compared to that of the control group (conspecific song: p = 1.62e -12 ; heterospecific song: p = 0.32; restricted mean survival time adjusted by Bonferroni).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used restricted mean time lost (RMTL) as an indicator of the cumulative copulation rate to evaluate this change, where a larger RMTL reflects higher copulation acceptance (Fig. 4 E ; See Materials and Methods for details) (15). We found that the response of experienced females to the conspecific song, but not to the heterospecific song, was significantly reduced in the Dop1R2 knockdown group when compared to that of the control group (conspecific song: p = 1.62e -12 ; heterospecific song: p = 0.32; restricted mean survival time adjusted by Bonferroni).…”
Section: Resultsmentioning
confidence: 99%
“…Fly pairs were recorded for 35 min at 15 fps with a web camera (Logicool HD Webcam C270, Tokyo, Japan). Copulation was defined as the following criteria: (1) the male mounts the female for more than 5 min, (2) the mounted female decreases locomotor activity, and (3) opens her wings during the mounting (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research in Poecilia reticulata has revealed differential gene expression in the brains of females in response to male attractiveness (i.e., colorful vs. dull males; Bloch et al, 2018). Similarly, studies on Drosophila have explored the neural circuits and differential gene expression in females' brains related to male courtship and/or female receptivity (Baker et al, 2022; Immonen & Ritchie, 2012; Kohl et al, 2013; Mezzera et al, 2020; Ning et al, 2022; Ohashi et al, 2023; Pacheco et al, 2021; Wang et al, 2020; Yang et al, 2023). However, much investigation is still needed to understand how male attractiveness affects the underlying mechanisms in female brains and their association with mate rejection and offspring production.…”
Section: Introductionmentioning
confidence: 99%